Hydride vapor phase epitaxy for gallium nitride substrate. (October 2019) - Hu, Jun; Wei, Hongyuan; Yang, Shaoyan; Li, Chengming; Li, Huijie; Liu, Xianglin; Wang, Lianshan; Wang, Zhanguo
Abstract: Due to the remarkable growth rate compared to another growth methods for gallium nitride (GaN) growth, hydride vapor phase epitaxy (HVPE) is now the only method for mass product GaN substrates. In this review, commercial HVPE systems and the GaN crystals grown by them are demonstrated. This article also illustrates some innovative attempts to develop homebuilt HVPE systems. Finally, the prospects for the further development of HVPE for GaN crystal growth in the future are also discussed.